Más allá del “conflicto”: Palestina y las estructuras profundas de la colonización global - Collins, John (Política y Sociedad, 2011)
This article seeks to relocate the analysis of violence in Palestine within an alternative paradigm that emphasizes long-term processes of global colonization. Beginning from the premise that Palestine is a site of an ongoing settler-colonial project (Zionism) rather than a simple “conflict,” it views contemporary realities as overdetermined by the deep structures that this project has put in place. Using the work of Paul Virilio as a key theoretical touchstone, it explores Palestine’s microcosmic and often prophetic embeddedness in three overlapping colonial modes: exocolonization (the colonization of territories outside one’s own), endocolonization (the colonization of specific populations within the territory under one’s control in the context of permanent or “pure” war), and dromocolonization (the colonization of humanity by techno-scientific acceleration). Examination of these three modes not only sheds light on Zionism’s specific colonial practices (e.g., the exclusion and confinement of Palestinians), but also encourages us to think beyond actor-centered conceptions of politics and consider the impact of processes (e.g., militarization or acceleration) that stretch beyond the control of rational actors. In particular, we see how Palestine has become a laboratory for new forms of warfare and social control whose global implications cannot be overestimated. With this in mind, the article concludes by arguing that an exploration of the challenges and possibilities of decolonization in Palestine can help us think through what global decolonization might mean.